2011
DOI: 10.1177/0731684411427483
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the ocean water immersion and UV ageing on the dynamic mechanical properties of the PPS/glass fiber composites

Abstract: Nowadays, the poly(phenylene sulfide) thermoplastic matrix composites have being utilized by most of the aerospace companies in order to replace a great quantity of the components made of aluminum, thermoset composites, or both and it is the reason they are being strongly considered to be utilized into marine structures, however, are quite often exposed to the environmental conditions that can damage them irreversibly, minimizing their qualities and compromising their performance. Depending on the aviation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…This means that, the specimens presented a weight gain during the exposure time since the water remains free over time and tends to penetrate in polymer matrix by the concentration gradient. Also, it initiates the relaxation process of the polymer chain and the hygrothermal filling of existing voids [35,36]. In this work, it was observed that after eight weeks of exposure in moisture environment the composites presented the follow average values of saturation points: the PPS/CF* laminate presented 0.165% and the PPS/BP/CF* laminate reached 0.307% of moisture, respectively.…”
Section: Calculation Of Density and Porosity Of The Composite Laminatementioning
confidence: 67%
“…This means that, the specimens presented a weight gain during the exposure time since the water remains free over time and tends to penetrate in polymer matrix by the concentration gradient. Also, it initiates the relaxation process of the polymer chain and the hygrothermal filling of existing voids [35,36]. In this work, it was observed that after eight weeks of exposure in moisture environment the composites presented the follow average values of saturation points: the PPS/CF* laminate presented 0.165% and the PPS/BP/CF* laminate reached 0.307% of moisture, respectively.…”
Section: Calculation Of Density and Porosity Of The Composite Laminatementioning
confidence: 67%
“…Moisture substantially affects the properties of fiber-reinforced plastic composites [9]. Water enters a composite material mainly by the process of diffusion.…”
Section: Influence Of Moisture On Mechanical Propertiesmentioning
confidence: 99%
“…This is probably due to the edge effects [5,[8][9][10][11]. This is probably due to the edge effects [5,[8][9][10][11].…”
Section: Influence Of Moisture On Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous investigations on the GF/PPS behavior after UV/ condensation exposure are found. De Faria et al [31] observed color variation and cracking of the surface after 1900 h of UV exposure. Costa et al [32] verified not only color variation and cracking of the surface, but also a 3% reduction in the ILSS after 900 h of UV/ condensation conditioning.…”
Section: Introductionmentioning
confidence: 99%